Spontaneous subcapsular renal hematoma as a cause of acute abdominal pain - a case report - Krunić, Nikola; Petković, Pavle; Jovanović, Filip; Dragičević, Tode; Jelić, Milica; Ilić, Slađana; Vojinović, Radiša (Medicinski časopis, 2025)
Spontaneous subcapsular renal hematoma (SSRH) is a potential cause of acute abdominal pain that does not represent a significant part in the etiology of acute abdominal pain. We present the case of a 69-year-old female patient who came to the surgical outpatient clinic because of sudden pain in the abdomen, predominantly right lumbar side. Ultrasonography revealed a heterogeneous change on the contour of the right kidney, and the diagnosis of subcapsular hematoma was confirmed by abdominal computed tomography (CT) scan. The cause of the hematoma could not be determined either by history (the patient mentions only arterial hypertension), or by laboratory or CT examination.